1974
DOI: 10.1021/ja00833a027
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of carbinolamine formation

Abstract: 41) The pK values of -8.1 and -6.7 for p-nitrobenzaldehyde and unsubstituted benzaldehyde, respectively, reported by Arnett, Quirk, and Lar-sen40 were determined from enthalpies of protonation in fluorosulfonic acid. These values are comparable with the values of -9.2 and -7.5 obtained by correction of the H0 values at half-protonation determined by Yates and Stewart42 to the scale of Jorgenson and Hartter,43 and the pK of -6.7 for benzaldehyde is in good agreement with that of -6.75 reported by Greig and John… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 6 publications
8
90
0
1
Order By: Relevance
“…7, also makes a hydrogen bond to the C 2 hydroxyl in the MBP structure and Substrate Cleavage-A multiple catalytic role for Glu-187 in FBP aldolase catalysis was advanced from enzymological data that implicated the residue in C 3 -C 4 bond cleavage as well as in proton transfers at the level of the ketimine intermediate (11). The structural analysis herein reveals Glu-187 participation in hydrogen bond formation with key reaction intermediates (7,45). A catalytic mechanism by which to promote cleavage of the C-C bond in class I FBP aldolases integrating enzymology and structure data is outlined in Scheme II.…”
Section: (ϳ08 å Inmentioning
confidence: 92%
“…7, also makes a hydrogen bond to the C 2 hydroxyl in the MBP structure and Substrate Cleavage-A multiple catalytic role for Glu-187 in FBP aldolase catalysis was advanced from enzymological data that implicated the residue in C 3 -C 4 bond cleavage as well as in proton transfers at the level of the ketimine intermediate (11). The structural analysis herein reveals Glu-187 participation in hydrogen bond formation with key reaction intermediates (7,45). A catalytic mechanism by which to promote cleavage of the C-C bond in class I FBP aldolases integrating enzymology and structure data is outlined in Scheme II.…”
Section: (ϳ08 å Inmentioning
confidence: 92%
“…Thus, experimental procedures for the preparation of aliphatic aldimines have become more specific in order to improve the yield 19 . The reaction mechanism of amine addition to carbonyl compounds in aqueous solution has been studied at the experimental level [20][21][22][23][24] , and some theoretical studies have been reported 25,26 . Sayer et al has proposed a general mechanism for this reaction in aqueous solution and at variable pH.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the primary and secondary amines react by nucleophilic addition with carbonyl compounds to give intermediate tetrahedral addition products called hemiaminals [14] as a first step of condensation reaction [15]. The next step is the dehydration of that compound which leads to the formation of stable imines, enamines, hydrazones and related compounds [16].…”
Section: Open Accessmentioning
confidence: 99%